Growing-season precipitation since 1872 in the coastal area of subtropical southeast China reconstructed from tree rings and its relationship with the East Asian summer monsoon system. (November 2017) - Cai, Qiufang; Liu, Yu; Liu, Han; Sun, Changfeng; Wang, Yanchao
Highlights: Tree-ring width in subtropical southeast China contains precipitation signal. The first growth-season precipitation was reconstructed for the past 141 years. Reconstruction captured the moisture signal in a broad region of southeast China. Abstract: Tree rings from temperate zones of the world have provided abundant palaeo- ecological and paleo-hydroclimatic information. However, tree rings from subtropical to tropical regions remain relatively scarce, which greatly limit our fully understanding about the climate change issues. In the present work, tree-ring-width (TRW) measurements of Masson pine from Fujian province, the coastal area of subtropical southeast China were successfully crossdated and a TRW STD chronology was developed from 1854 to 2012. Significantly positive correlation was identified between the tree rings and April–November total precipitation ( r  = 0.71, p <  0.01). The reconstructed April–November precipitation exhibited two comparatively wet (1876–1886 and 1957–1962) and one comparatively dry (1986–2004) periods. An evident drying trend since 1959 was seen and it was mitigated after 1993. Most of the extreme low-precipitation years in the reconstruction were supported by the historical records. As revealed by the spatial correlation patterns, our precipitation reconstruction was also consistent with other hydroclimatic records along the coastal areas of southeast China, proving its ability to capture the large-scale hydrological signal in southeast China (mainly refers to the south of the middle-lower reaches of Yangtze River). The reconstructed precipitation showed significant correlation with the East Asian summer Monsoon (EASM) index. Moreover, it also indicated simultaneous variation with the monsoon precipitation in North China on a decadal scale, implying that growing season precipitation variations in both regions were influenced by the EASM strength. This work highlights the potential of using tree-ring width to reconstruct precipitation in subtropical southeast China, while the relevant issues about precipitation variation in this region is far from resolved.